An investigation into influence of physical and chemical surface modification of macro-polypropylene fibers on properties of cementitious composites. (30th May 2020) - Rostami, Rouhollah; Zarrebini, Mohammad; Sanginabadi, Khaled; Mostofinejad, Davood; Mahdi Abtahi, Sayyed; Fashandi, Hossein
Highlights: Influence of physical and chemical surface modification of fibers on properties of cementitious composites. Fiber reinforced concrete as a cementitious composites were designed, produced and studied. Hydrophobic and hydrophilic polypropylenes fibers were made. The surface of fibers was physically modified by surface indentation. Abstract: During the past decades the use of polymeric fibers known as macro-fibers has been welcomed. The interface between these fibers and the cementitious matrix fundamentally influences the properties of the resultant composites. The induced indentation on the surface of macro-fibers enhances the adhesion of the fiber-matrix at the interface. Additionally hydrophilic fibers tend to adhere more positively with concrete matrix. In this research, hydrophobic and hydrophilic polypropylene fibers were made using ordinary and grafted anhydride maleic polypropylene granules. The surface of fibers was physically modified by surface indentation. Properties of the produced fibers, together with their moisture absorption tendency were determined. Various concrete mix designs were prepared with 0.55% fiber volume fraction. The concrete samples were tested for workability, compressive, splitting tensile and flexural strength. Results showed that the use of indented and hydrophilic fibers improves the mechanical properties of the reinforced concrete. The increase in flexural strength in case of indented and hydrophilic fibers was found to be 77%. The area under load-displacement curve as representation of the amount of energy absorption capacity were evaluated. The results pointed to 9 times increase in energy absorption capacity of the samples reinforced with indented and hydrophilic fibers in comparison with that of control sample. Additionally it was found that the effect of hydrophilicity of fibers on energy absorption capacity of the concrete is more pronounced than the surface indentation.